Assessment of syndromic management of curable sexually transmitted and reproductive tract infections among pregnant women: an observational cross-sectional study - Enesia Banda Chaponda; Jane Bruce; Charles Michelo; Daniel Chandramohan; R. Matthew Chico (BMC, 2021)
Abstract Background This study estimated the prevalence of curable sexually transmitted and reproductive tract infections (STIs/RTIs) among pregnant women attending antenatal care (ANC) in rural Zambia, evaluated the effectiveness of syndromic management of STIs/RTIs versus reference-standard laboratory diagnoses, and identified determinants of curable STIs/RTIs during pregnancy. Methods A total of 1086 pregnant women were enrolled at ANC booking, socio-demographic information and biological samples were collected, and the provision of syndromic management based care was documented. The Piot-Fransen model was used to evaluate the effectiveness of syndromic management versus etiological testing, and univariate and multivariate logistic regression analyses were used to identify determinants of STIs/RTIs. Results Participants had a mean age of 25.6 years and a mean gestational age of 22.0 weeks. Of 1084 women, 700 had at least one STI/RTI (64.6%; 95% confidence interval [CI], 61.7, 67.4). Only 10.2% of infected women received any treatment for a curable STI/RTI (excluding syphilis). Treatment was given to 0 of 56 women with chlamydia (prevalence 5.2%; 95% CI, 4.0, 6.6), 14.7% of participants with gonorrhoea (prevalence 3.1%; 95% CI, 2.2, 4.4), 7.8% of trichomoniasis positives (prevalence 24.8%; 95% CI, 22.3, 27.5) and 7.5% of women with bacterial vaginosis (prevalence 48.7%; 95% CI, 45.2, 51.2). An estimated 7.1% (95% CI, 5.6, 8.7) of participants had syphilis and received treatment. Women < 20 years old were more likely (adjusted odds ratio [aOR] = 5.01; 95% CI: 1.23, 19.44) to have gonorrhoea compared to women ≥30. The odds of trichomoniasis infection were highest among primigravidae (aOR = 2.40; 95% CI: 1.69, 3.40), decreasing with each subsequent pregnancy. Women 20 to 29 years old were more likely to be diagnosed with bacterial vaginosis compared to women ≥30 (aOR = 1.58; 95% CI: 1.19, 2.10). Women aged 20 to 29 and ≥ 30 years had higher odds of infection with syphilis, aOR = 3.96; 95% CI: 1.40, 11.20 and aOR = 3.29; 95% CI: 1.11, 9.74 respectively, compared to women under 20. Conclusions Curable STIs/RTIs were common and the majority of cases were undetected and untreated. Alternative approaches are urgently needed in the ANC setting in rural Zambia.